Comparison of two trunk electromagnetic sensor placement methods during shoulder motion analysis. (8th February 2018) - Plummer, Hillary A.; Pozzi, Federico; Michener, Lori A.
Abstract: For kinematic studies of the shoulder, electromagnetic sensors are commonly placed on the humerus, scapula, and trunk. The trunk sensor is used to describe humeral and scapular kinematics with respect to the trunk. There are two common trunk sensor placements, the sternum or third thoracic vertebrae (T3). It is currently unclear if placement of the trunk sensor affects kinematics, making it difficult to compare data across studies. The purpose of this study was to compare two trunk sensor placements (T3 and sternum) on trunk and scapular kinematics during arm elevation. An electromagnetic tracking system was used to collect kinematic data during five consecutive repetitions of ascending and descending arm elevation in the sagittal plane. The results indicate that trunk sensor placement had no significant effect on trunk kinematics or scapular upward/downward rotation and internal/external rotation. Scapular anterior/posterior tilt was significantly greater when the trunk sensor was on the sternum compared to the T3 vertebrae during ascending 30°–120°: mean difference = −3.51° (95%CI: −5.61, −1.40), and descending 120°–30°: mean difference = −3.27° (95%CI: −6.07, −0.48). However, the difference in anterior/posterior tilt did not exceed the error (minimal detectable change), and thus is likely not a meaningful difference. These results indicate the trunk sensors can be affixed on T3 or the sternum, depending on the needs of the study.